2013
DOI: 10.1111/cei.12085
|View full text |Cite
|
Sign up to set email alerts
|

Progress in immune-based therapies for type 1 diabetes

Abstract: SummaryImmune-based therapies that prevent type 1 diabetes or preserve metabolic function remaining at diagnosis have become a major objective for funding agencies and international trial consortia, and receive backing from notable patient advocate groups. The development of immune-based therapeutic strategies in this arena requires a careful balancing of the risks of the therapy against the potential benefits, because many individuals are diagnosed or identified as being at increased risk of disease in early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 123 publications
0
42
0
Order By: Relevance
“…With this in mind, a number of studies over the past 30 years have attempted to preserve beta cell function in patients with type 1 diabetes [5]. Many of these trialled agents act through 'suppressing' the inflammatory autoimmune process that targets the beta cell.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, a number of studies over the past 30 years have attempted to preserve beta cell function in patients with type 1 diabetes [5]. Many of these trialled agents act through 'suppressing' the inflammatory autoimmune process that targets the beta cell.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive research, tested treatments have this far at best only temporarily arrested the progressive loss of b-cells in type 1 diabetes (1). Retention of endogenous insulin secretion is an attractive goal, since it causes better glycemic control (2) and decreases the risk of microvascular complications and severe hypo-or hyperglycemia episodes (3,4).…”
mentioning
confidence: 99%
“…Therefore, patients need life-long insulin replacement therapy to control blood glucose levels. In the past, various efforts have been undertaken to develop and assess strategies that halt disease progression [1]. Immunotherapeutic strategies have aimed either at systemic downmodulation of the immune system or targeting specific autoimmune mechanisms involved in the disease.…”
mentioning
confidence: 99%
“…The calcineurin inhibitor cyclosporine A was among the first nonspecific immune suppressants to be used in T1D. Continuous treatment initiated soon after disease onset demonstrated that it was possible to preserve b-cell function, with patients experiencing insulin independency [1]. However, this effect was short lasting and associated with accelerated renal dysfunction [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation